The Effect of incentives on employee performance with motivation as a moderation variable - Setyowati Subroto; Agnes Dwita Susilawati; Yuniarti Herwinarni; Evit Wijaya Ali (Institute of Computer Science (IOCS), 2023)
Business competition has become a very natural thing nowadays among existing companies and it is inevitable anymore. All companies are required to be ready to face it in any way such as making improvements and improving the company's internal and external conditions to be able to survive and succeed in facing existing competition. One of the internal conditions that must receive attention from the company is the human resources factor. This study purpose to analyze the influence of incentives on performance, the influence of incentives on motivation, the influence of motivation on performance and the influence of incentives on performance with motivation as a mediator. This research employed a quantitative approach, types of data collection, the sample in this study was 45 respondents, using simple linear analysis test data analysis, and a sobel test. This study found thati nsentif affects employee performance, insentif affects work motivation, motivation affects employee performance and insentif affects performance with motivation as a mediator at PT Matahari Department Store Pasific Mall Tegal.